Strategies for Designing and Monitoring Malaria Vaccines Targeting Diverse Antigens - Barry, Alyssa E.; Arnott, Alicia (Frontiers in Immunology, 2014)
After more than 50 years of intensive research and development, only one malaria vaccine candidate, “RTS,S”, has progressed to Phase 3 clinical trials. Despite only partial efficacy, this candidate is now forecast to become the first licensed malaria vaccine. Hence, more efficacious second-generation malaria vaccines that can significantly reduce transmission are urgently needed. This review will focus on a major obstacle hindering development of effective malaria vaccines: parasite antigenic diversity. Despite extensive genetic diversity in leading candidate antigens, vaccines have been and continue to be formulated using recombinant antigens representing only one or two strains. These vaccine strains represent only a small fraction of the diversity circulating in natural parasite populations, leading to escape of non-vaccine strains and challenging investigators’ abilities to measure strain-specific efficacy in vaccine trials. Novel strategies are needed to overcome antigenic diversity in order for vaccine development to succeed. Many studies have now catalogued the global diversity of leading Plasmodium falciparum and Plasmodium vivax vaccine antigens. In this review, we describe how population genetic approaches can be applied to this rich data source to predict the alleles that best represent antigenic diversity, polymorphisms that contribute to it, and to identify key polymorphisms associated with antigenic escape. We also suggest an approach to summarise the known global diversity of a given antigen to predict antigenic diversity, how to select variants that best represent the strains circulating in natural parasite populations and how to investigate the strain-specific efficacy of vaccine trials. Use of these strategies in the design and monitoring of vaccine trials will not only shed light on the contribution of genetic diversity to the antigenic diversity of malaria, but will also maximise the potential of future malaria vaccine candidates.